Child transport injuries and deaths in Lebanon: a multicentre retrospective study - Khalil El Asmar; Samar Al-Hajj; Sebouh Arjinian; Zahraa Hamadeh; Elie Al-Zaghrini (BMJ Open)
Introduction Road traffic injury (RTI) constitutes the leading cause of deaths and disabilities for individuals aged 5–29 years globally. Lebanon suffers from a high toll of transport mortality and morbidity, though accurate and reliable RTI data are limited. The aim of this study is to assess the prevalence and the characteristics of child transport injuries and deaths in Lebanon and to determine their outcomes and associated risk factors.Methods We conducted a multicentre retrospective study to analyse data on transport injuries and deaths for children aged 0–17 years over a 3-year period (2015–2017). Data were captured from multiple sources, including police reports and the emergency departments of 30 hospitals across the country . We performed logistic regression models to examine the effects and test the association of multiple simultaneous factors on the child injury outcome and severity.Results A total of 3,033 cases of child transport injuries and 237 fatalities were collected. The majority of the cases were males (73%) (mean (SD) age=11 (±5) years). Transport victims were Lebanese (66.5%) and Syrian refugees (27.9%). The most commonly reported factor contributing to child’s RTI was a child riding in high-speed vehicles (25%) and the most affected body regions were upper and lower extremities (29.9%), followed by head injuries (26.1%). Pedestrians had higher odds of sustaining fatal injuries compared to four-wheel vehicle occupants (OR=1.6; 95% CI: 1.17 to 2.27). Older age groups of 6–14 years (OR=0.51; 95% CI: 0.79 to 0.69) and 15–17 years (OR=0.41; 95% CI: 0.30 to 0.61) had lower odds of dying from transport injuries compared to the younger age group of 0–5 years.Conclusion Child transport injury is a major public health problem in Lebanon. Findings from this study urge policy-makers and health professionals to implement evidence-based child transport safety policies and behaviour change programs to reduce child transport injuries and deaths.